Child-Friendly School Management: A Study of Ukhuwah Wathoniyah at Ma'arif Nahdlatul Ulama - Apologia, Milla Ahmadia; M. Mochtar Mas’od; Ali Masykuri; Anita Hidayati; Verriyanto Eko Priyono Putra (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This article aims to describe and explain the management of child-friendly schools which is a real implementation of ukhuwah wathoniyah in several schools assisted by the Branch Board of Ma'arif Nahdlatul Ulama Education Institution Sidoarjo, namely: MI NU KH Mukmin, MI NU Pucang, and MI Darun Najah Sukodono, Madrasah Tsanawiyah NU Sidoarjo, and Taruna Tarik Vocational High School. This management process includes planning, organizing, implementing, monitoring, and the role of various parties such as principals, teachers, parents, and external parties in supporting child-friendly school programs. In planning, indicators of child-friendly school implementation are created by the eight national education standards. This research uses a descriptive qualitative approach by collecting data through observation, interviews, and documentation. The results reflect the school's seriousness in implementing the concept of child-friendly schools as an integral part of ukhuwah wathoniyah. The program not only involves the internal school but also involves active participation from parents and external parties. Thus, child-friendly school management in schools assisted by the Branch Manager of the Ma'arif Nahdlatul Ulama Educational Institution in Sidoarjo can be considered an inspiring model and has a positive impact on the education of children in the neighborhood.